Event-prediction of right ventricular to pulmonary circulation coupling measured during exercise in patients with heart failure. (25th November 2020) - Sugimoto, T; Boveri, S; Bandera, F; Barletta, M; Alfonzetti, E; Guazzi, M
Abstract: Background: Right ventricular (RV) contractile function and its coupling with pulmonary circulation (PC) stratify the pattern of clinical phenotypes in heart failure (HF) but its predictive role when measured during exercise is undefined. This study sought to investigate the prognostic impact of RV to PC coupling during exercise in HF patients of any left ventricular ejection fraction (LVEF) categorization. Methods: 218 HF patients with reduced (n=120), mid-range (n=55), and preserved (n=43) EF and 51 patients with noncardiac dyspnea underwent exercise with gas exchange analysis combined with echocardiography for assessment of RV-PC coupling assessed by the TAPSE/PASP ratio and left atrial (LA) strain (as a mediator of RV to PC uncoupling). Results: TAPSE was negatively correlated with PASP (R=−0.31 and −0.31, P<0.001) both at rest and during exercise. TAPSE/PASP was positively correlated with LA strain (R=0.58 and 0.59, P<0.001) and cardiac output (R=0.28 and 0.58, P<0.001) both at rest and during exercise. The severity of mitral regurgitation was also associated with TAPSE/PASP and LA strain both at rest and during exercise (P for trend <0.001). There was significant difference in peak VO2 and the minute ventilation-carbon dioxide production slope among 3 groups divided by tertile of TAPSE/PASP at exercise. During 5 years follow up, 48 HF patients with reduced (n=34), mid-range (n=8), and preserved (n=6) EF had the composite end point. The age and gender adjusted hazard ratio for the events in HF patients with TAPSE/PASP at exercise <0.33, derived by ROC curve (AUC=0.71, P<0.05), was 2.9 (95% CI: 1.5 to 5.5, figure). Conclusions: The impaired RV to PC coupling by TAPSE/PASP ratio during exercise predicts prognosis in patients with HF. The cutoff of 0.33 overlaps with the threshold observed to be predictive at rest in various reports across HF populations. These data further emphasize the usefulness of assessing RV to PC uncoupling in cardiac failure during various clinical conditions. Funding Acknowledgement: Type of funding source: None